Wound-healing activity of solvent fractions and antiinflammatory activity of crude extract and solvent fractions of Acokanthera schimperi Schweinf (Apocynaceae) leaves in mice model - Workineh Woldeselassie Hammeso; Tesfaye Yimer; Getnet Tadege; Wakuma Wakene Jifar; Dejen Nureye (Elsevier, 2025)
Background: In Ethiopia, Acokanthera schimperi is frequently used to treat wounds and other conditions. Nothing has been published to date on the anti-inflammatory properties of A. schimperi leaves or the wound-healing effects of solvent fractions, despite a report on the crude extract's ability to heal wounds being available in the literature. Purpose: Therefore, this experiment has been initiated to look into the solvent fractions' ability to heal wounds and the anti-inflammatory properties of the A. schimperi leaf 80 % methanol extract and its fractions in mice. Study design: The experimental study design was conducted to evaluate wound healing and the anti-inflammatory properties of the A. schimperi leaf 80 % methanol extract and its fractions in mice. Methods: The plant's leaf crude extract was fractionated using ethyl acetate, chloroform, and distilled water. The resulting fractions were then combined with a simple ointment base to make an ointment at 5 % and 10% w/w. Next, using excision and incision wound models, the ointments' ability to promote wound healing was assessed. The excision model was utilized to estimate wound contraction and epithelization time, whereas the incision model was utilized to measure tensile strength. By dissolving 1 % carrageenan in 0.9 % saline (w/v) and giving oral dosages of the crude extract and solvent fractions (100, 200, and 400 mg/kg), the anti-inflammatory efficacy of the leaves was assessed concurrently with a carrageenan-induced hind paw edema model. Results: Significant wound healing activity was seen in both models in wounds treated with 5 % and 10 % (w/w) solvent fraction ointment, as shown by higher tissue breaking strength (with 51.38 % maximum effect by 10 % (w/w) ethyl acetate fraction ointment), shorter epithelization times (within 15.92 days by ethyl acetate fraction ointment 10 %), and increased wound contraction (99.40 % by ethyl acetate fraction ointment 10 %). The extract (hydromethanolic) and solvent fractions also showed notable dose-related decreases in inflammation. Conclusion: The study's findings supported A. schimperi's traditional use as a wound healing agent by showing that the solvent fractions of the plant's leaves promoted wound healing, at least in part, through their anti-inflammatory effect.